2015
DOI: 10.1038/nature15398
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic control of sensory selection in divided attention

Abstract: How the brain selects appropriate sensory inputs and suppresses distractors is a central unsolved mystery in neuroscience. Given the well-established role of prefrontal cortex (PFC) in executive function1, its interactions with sensory cortical areas during attention have been hypothesized to control sensory selection2–5. To test this idea and more generally dissect the circuits underlying sensory selection, we developed a cross-modal divided attention task in mice enabling genetic access to this cognitive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
436
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(472 citation statements)
references
References 41 publications
34
436
0
2
Order By: Relevance
“…The validation gate predicts that top-down control over input processing includes the suppression of input by defining regions of no subjective interest rather than solely defining a positive region of interest. Indeed, it has recently been shown that the rodent equivalent of the prefrontal cortex (PFC) directly controls input processing in a taskspecific way by driving activity in the sensory zone of the thalamic reticular nucleus [185]. In this way, we can distinguish attention, which in this case acts via an inhibitory cortico-thalamic and an excitatory cortico-cortical pathway, from the access of states to consciousness.…”
Section: (C) Empirical and Methodological Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The validation gate predicts that top-down control over input processing includes the suppression of input by defining regions of no subjective interest rather than solely defining a positive region of interest. Indeed, it has recently been shown that the rodent equivalent of the prefrontal cortex (PFC) directly controls input processing in a taskspecific way by driving activity in the sensory zone of the thalamic reticular nucleus [185]. In this way, we can distinguish attention, which in this case acts via an inhibitory cortico-thalamic and an excitatory cortico-cortical pathway, from the access of states to consciousness.…”
Section: (C) Empirical and Methodological Consequencesmentioning
confidence: 99%
“…Hence, this fMRI study reveals a circuit for selective prediction-based inhibitory filtering that the validation gate hypothesis proposes, which directly supports the idea that the fronto-parietal system can be considered the substrate of an autonomous consciousness memory system that can selectively couple and uncouple from sensory processing. This latter feature is further invoked by the long-range collaterals that can be found in the thalamocortical projections of the prefrontal cortex onto the reticular nucleus of sensory thalamic nuclei facilitating the task specific inhibition of feed-forward sensory processing [184,185].…”
Section: (C) Empirical and Methodological Consequencesmentioning
confidence: 99%
“…Wimmer et al (47) provided fluorometric data on [Cl − ] i changes in vivo by using SuperClomeleon (48), which has a somewhat higher affinity (20-40 mM) to Cl − than Clomeleon. This study has important differences from our approach, since they could only measure bulk changes of [Cl − ] i concentration in a relatively large brain volume.…”
Section: Discussion Properties and Advantages Of Lssmclophensor In Nementioning
confidence: 99%
“…Previous studies have found that the attention system is related to a variety of cortical areas, including the occipital cortex, PPC, FEF, aI/VLPFC, dACC and DLPFC; and, subcortically: the thalamus and the SC Eckstein, 2011;Saalmann and Kastner, 2011;Kim et al, 2012;Petersen and Posner, 2012;Zénon and Krauzlis, 2012;Krauzlis et al, 2013;Squire et al, 2013;Purcell et al, 2013;Peleen and Kastner, 2014;Cieslik et al, 2015;Katsuki and Constantinidis, 2015;Wimmer et al, 2015). Our fMRI data analysis results confirmed our hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…For instance, LGN activity is modulated by selective attention and has been related to the allocation of attention focus in specific visual field locations (O'Connor, Fukui, Pinsk and Kastner, 2002); the pulvinar nucleus is relevant for visuo-spatial functions that involve reorienting attention and spatial coding, and the reticular nucleus modulates LGN and pulvinar with inhibitory signals and seems to exert control over the retino cortical and cortico-thalamo-cortical pathways (Saalmann and Kastner, 2011). Indeed, recent studies show that the reticular nucleus receives inputs from the prefrontal cortex to then bias the activity of the other visual thalamic nuclei during sensory selection processing (Wimmer et al, 2015). Increased thalamic activation has been found during the performance of visuo-spatial tasks (compared to baseline or control conditions).…”
Section: Thalamusmentioning
confidence: 99%